Why is women's utilization of a publicly funded health insurance low?: a qualitative study in Tamil Nadu, India - Rajalakshmi RamPrakash; Lakshmi Lingam (BMC, 2021)
Abstract Background The continuing impetus for universal health coverage has given rise to publicly funded health insurance schemes in lower-middle income countries. However, there is insufficient understanding of how universal health coverage schemes impact gender equality and equity. This paper attempts to understand why utilization of a publicly funded health insurance scheme has been found to be lower among women compared to men in a southern Indian state. It aims to identify the gender barriers across various social institutions that thwart the policy objectives of providing financial protection and improved access to inpatient care for women. Methods A qualitative study on the Chief Minister's Comprehensive Health Insurance Scheme was carried out in urban and rural impoverished localities in Tamil Nadu, a southern state in India. Thirty-three women and 16 men who had a recent history of hospitalization and 14 stakeholders were purposefully interviewed. Transcribed interviews were content analyzed based on Naila Kabeer's Social Relations Framework using gender as an analytical category. Results While unpacking the navigation pathways of women to utilize publicly funded health insurance to access inpatient care, gender barriers are found operating at the household, community, and programmatic levels. Unpaid care work, financial dependence, mobility constraints, and gender norms emerged as the major gender-specific barriers arising from the household. Exclusions from insurance enrollment activities at the community level were mediated by a variety of social inequities. Market ideologies in insurance and health, combined with poor governance by State, resulted in out-of-pocket health expenditures, acute information asymmetry, selective availability of care, and poor acceptability. These gender barriers were found to be mediated by all four institutions-household, community, market, and State-resulting in lower utilization of the scheme by women. Conclusions Health policies which aim to provide financial protection and improve access to healthcare services need to address gender as a crucial social determinant. A gender-blind health insurance can not only leave many pre-existing gender barriers unaddressed but also accentuate others. This paper stresses that universal health coverage policy and programs need to have an explicit focus on gender and other social determinants to promote access and equity.